2012
DOI: 10.4067/s0717-95022012000100038
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Forms among Three Dominant Ethnic Groups of Gombe State, Nigeria

Abstract: SUMMARY:Anthropometric measurements such as cranial and facial forms provide essential information that can be used added provide in orofacial surgery and in diagnostic comprehension between patient and normal populations. There is no published literature about the types of head and face shapes in Fulani, Tangale and Tera ethnic groups of Nigeria. Hence, this study was undertaken to document the various cranial and facial forms of these ethnic groups residing in Gombe region of North-Eastern Nigeria. Head leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 11 publications
2
13
1
Order By: Relevance
“…This is in line with the present findings which also reported prosopic indices in males (PI 90.66) and females (PI 96 .15), the incidence doesn't differ to any noteworthy degree from Maina et al 10 findings. Farahani et al 11 on estimation of facial indices in males 19-20years old reported that the dominant type of face shape of males aged 19-20years was mesoprosopic agrees with our findings.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is in line with the present findings which also reported prosopic indices in males (PI 90.66) and females (PI 96 .15), the incidence doesn't differ to any noteworthy degree from Maina et al 10 findings. Farahani et al 11 on estimation of facial indices in males 19-20years old reported that the dominant type of face shape of males aged 19-20years was mesoprosopic agrees with our findings.…”
Section: Discussionsupporting
confidence: 82%
“…Jahanshahi's et al 9 study on Fars and Turkmans of Iran revealed that they had mesoprosopic to euriprosopic round face contradict our findings. Maina et al 10 on craniofacial forms among three dominant ethnic group of Gombe state, Nigeria reported facial shape of Fulani males and females were hyperleptoprosopic (PI>95); Tangale males and females were both leptoprosopic (PI between 90 and 94.9); Tera males were leptoprosopic (PI 94.1) while their females were hyperleptoprosopic (PI 102.4). However, total mean prosopic indices in all males (PI 93.7) and females (PI 98.1) of the three tribes placed them in the leptoprosopic and hyperleptoprosopic groups respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study showed that facial height values obtained in this study (13.22 ± 0.86 cm, males and 12.45 ± 0.69 cm, females) were numerically lower but not statistically significant from that of a population in the Northeastern part of Nigeria (14.12 cm ± 0.75 in males and 14.13 cm ± 0.76 in females) [26], Sri Lanka population (14.02 ± 1.03 cm in males and 13.88 ± 1.29 cm in females) [27] and Indian population (13.00 ± 0.72 cm in males and 12.54 ± 0.6 cm in females) [28]. However, the results obtained for this parameter were significantly higher than that of the Bini ethnic group in Southsouth Nigeria (11.24 ± 0.46 cm, males and 11.12 ± 0.58 cm, females) [12] and Haryanvi adults in India (11.74 ± 0.70 cm in males and 10.21 ± 0.94 cm in females) [29].…”
Section: Resultsmentioning
confidence: 68%
“…Results of the present study using cephalometric indices namely the head length, head width, age, bizygomatic distance, upper facial, lower facial length, total facial length, nose width and skull height can be successfully used to predict anthropometric relationships between the two ethnic groups. [18,19,20]. Some of the parameters studied showed statistical significant difference between the two tribes of Igede and Idoma ethnic groups of Benue State, Nigeria.…”
Section: Discussionmentioning
confidence: 84%